Pneumonia - Rezaei, Nima (Infectious Diseases, 2022)
Pneumonia is an infectious disease of the pulmonary alveoli that leads to extensive morbidity and mortality. This book presents a comprehensive overview of this disease with chapters on hospital-acquired pneumonia, drug-related problems and hospital readmissions, secondary bacterial infections in viral pneumonia, and iron acquisition in pneumococci.